Impacts of air pollution, temperature, and relative humidity on leukocyte distribution: an epigenetic perspective - Gao, Xu (Environ Int, 2019)
BACKGROUND: Exploring the associations of air pollution and weather variables with blood leukocyte distribution is critical to understand the impacts of environmental exposures on the human immune system. OBJECTIVES: As previous analyses have been mainly based on data from cell counters, which might not be feasible in epidemiologic studies including large populations of long-stored blood samples, we aimed to expand the understanding of this topic by employing the leukocyte distribution estimated by DNA methylation profiles. METHODS: We measured DNA methylation profiles in blood samples using Illumina HumanMethylation450 BeadChip from 1,519 visits of 774 Caucasian males participating in the Normative Aging Study. Leukocyte distribution was estimated using Houseman’s and Horvath’s algorithms. Data on air pollution exposure, temperature, and relative humidity within 28 days before each blood draw was obtained. RESULTS: After fully adjusting for potential covariates, PM(2.5), black carbon, particle number, carbon monoxide, nitrogen dioxide, sulfur dioxide, temperature, and relative humidity were associated with the proportions of at least one subtype of leukocytes. Particularly, an interquartile range-higher 28-day average exposure of PM(2.5) was associated with 0.147-, 0.054- and 0.101-unit lower proportions (z-scored) of plasma cells, naïve CD8+ T cells, and natural killers, respectively, and 0.059- and 0.161-unit higher proportions (z-scored) of naïve CD4+ T cells and CD8+ T cells, respectively. CONCLUSIONS: Our study suggests that short-term air pollution exposure, temperature, and relative humidity are associated with leukocyte distribution. Our study further provides a successful attempt to use epigenetic patterns to assess the influences of environmental exposures on human immune profiles.